Mechanical doping of ZnO powders - Damonte, Laura Cristina (2012)
Massive Zn 1-xFe xO ternary oxides were prepared by mechanical milling from different starting materials as Fe 2O 3, α-Fe or FeO. The influence of different preparation conditions, such as initial concentrations, atmosphere and milling times on final products was investigated. The structure evolution and dopant incorporation in the wurtzite crystalline structure with milling time was analyzed by means of X-ray diffraction. The sample's magnetic character investigated by measurements in a Quantum Design MPMS-5S superconducting quantum interference device (SQUID) magnetometer consists of two superimposed signals, a ferromagnetic and a paramagnetic one. © 2011 Elsevier B.V. All rights reserved.